Video Compression using Key Frame Extraction for Improving Frame Resolution - Jasmine, J.; S. Annadurai, Dr. (International Journal of Engineering and Technology, 2018)
Histogram equalization is a strategy for modifying picture forces to improve differentiate. In the current work a histogram-based region saving CE technique is defined as an improvement issue to protect areas of the histogram for performing picture CE. The keyframe extraction issue utilizing Generalized Gaussian Density (GGD) parameters of wavelet change subbands alongside Kullback-Leibler remove (KLD) estimation. Shot and group limits are chosen utilizing KLDs between GGD highlight vectors, and after that keyframes are found dependent on similitude and disparity criteria. The area protecting property makes the histogram state of the upgraded picture to be like that of the first picture and still it will in general showcase extreme improvement and perform unnatural antiquities on pictures with high crests in their histograms. In this paper, we present a Modified SPIHT (Set parceling in various leveled trees) picture pressure calculation to give yield picture with best outcomes. Objective and emotional assessments demonstrate the high precision of this new methodology of consolidating SPIHT calculation and keyframes to differentiate upgrade contrasted with conventional strategies.Â